Aluminum recycling - Schlesinger, Mark E. (Taylor & Francis, 2014)
What makes this book unique is a specific focus on aluminum recovery, rather than just recycling in general. It also offers an integrated discussion of scrap recovery and re-melting operations and includes economic as well as technical elements of recycling. Important topics include a discussion of the scrap aluminum marketplace and how secondary aluminum is collected and sorted, the design and operation of furnaces for melting scrap, the refining of molten aluminum, and the recovery and processing of dross from re-melting operations. This second edition features more information on aluminu.